1998
DOI: 10.1002/jor.1100160208
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a stable articular cartilage phenotype without evidence of hypertrophy by adult human articular chondrocytes in vitro

Abstract: Chondrocytes that were isolated from adult human articular cartilage changed phenotype during monolayer tissue culture, as characterized by a fibroblastic morphology and cellular proliferation. Increased proliferation was accompanied by downregulation of the cartilage-specific extracellular matrix proteoglycan, aggrecan, by cessation of type-II collagen expression, and by upregulation of type-I collagen and versican. This phenomenon observed in monolayer was reversible after the transfer of cells to a suspensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
116
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(124 citation statements)
references
References 34 publications
7
116
0
1
Order By: Relevance
“…The higher baseline of type I1 collagen expression in monolayer chondrocyte cultures may magnify methylprednisolone-induced suppression. Maintaining a rounded morphology [5,7,24] and integrity of the cartilage extracellular matrix [9,22,44,49] supports stability of the chondrocytic phenotype in culture and may lessen the effects of corticosteroid exposure. Finally, although the articular cartilage was selected only from weight-bearing locations, neither the explant nor isolated chondrocyte culture systems can address the cellular heterogeneity of articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher baseline of type I1 collagen expression in monolayer chondrocyte cultures may magnify methylprednisolone-induced suppression. Maintaining a rounded morphology [5,7,24] and integrity of the cartilage extracellular matrix [9,22,44,49] supports stability of the chondrocytic phenotype in culture and may lessen the effects of corticosteroid exposure. Finally, although the articular cartilage was selected only from weight-bearing locations, neither the explant nor isolated chondrocyte culture systems can address the cellular heterogeneity of articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Using an in vivo model of synovitis, we showed that one dose of intraarticular MPA significantly decreased steady-state type I1 procollagen mRNA in articular cartilage [34]. Protein analyses in cartilage explants from these same animals, however, demonstrated increased total collagen synthesis in MPA-treated joints [5 11. An earlier study, using cartilage explants and metabolic labeling observed concentration-dependent effects of methylprednisolone.…”
mentioning
confidence: 99%
“…Adult human articular chondrocytes were isolated from healthy cartilage tissue [National Disease Research Interchange Tissue Bank (NDRI), Philadelphia, PA] from three donors aged 24, 31, and 52 years, as described previously (Binette et al, 1998). Briefly, tissue samples were minced and digested in 0.1% collagenase (Sigma, St. Louis, MO) for 18 hr at 37°C.…”
Section: Materials and Methods Cell Culturementioning
confidence: 99%
“…The morphological changes caused by suspension culture are accompanied by a simultaneous down-regulation of genes that are characteristic of proliferating fibroblasts and an up-regulation of cartilage specific genes, a process termed redifferentiation, which occurs over a period of several weeks (Binette et al, 1998;Yaeger et al, 1997). Because the molecular mechanisms involved in the modulation of the articular chondrocyte phenotype were not well established, we employed a subtractive hybridization strategy to generate cDNA libraries of genes that are differentially regulated between monolayer and suspension cultures of articular chondrocytes Gurskaya et al, 1996).…”
mentioning
confidence: 99%
“…hMSCs have advantages because of their availability and multipotency, but the effects of donor age and health are still not well understood [57], and these cells have less capacity to form cartilage than chondrocytes [58]. By contrast, harvesting of adult autologous articular chondrocytes involves joint biopsy, and the cells tend to dedifferentiate during expansion [35,59]. Approaches currently being studied include growth factor supplementation during cell expansion and culture [60,61], use of additional cell sources (such as nasal, ear and rib cartilage) [62], adipose-derived hMSCs [24] and cell co-culture [27,63].…”
Section: Summary and Future Directionsmentioning
confidence: 99%